Traffic Analysis Due To Development on Off Ramp Becakayu Highway - Amar Mufhidin; Eviani Subiastuti (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
The kalimalang highway is a connecting road between the city of Jakarta and Bekasi, the high mobility of passenger vehicles and goods is a problem of congestion that must be minimized. The volume of vehicles on the Kalimalang highway has increased quite high each year, but this has not been matched by growth in capacity. Therefore the government plants to build the Becakayu toll road to reduce congestion. This study aims to determine bottlenecks that occur due to the construction of an off-ramp on the Becakayu toll road, especially in section 2A, which is located on Jl. Veteran, while the location under review is the intersections affected by the construction of the off-ramp including the intersection of four signaling BCP, intersection of four signaling Veteran and Sarbini unsigned intersection, Data analysis in this study uses the MKJI 1997 method. From this method displays the behavior of traffic, for signal intersections will display signal time, capacity, vehicle stopped ratio, queue length, and average delay and for unsignalized intersections will display capacity, average delay and queue opportunity. From the results of this study it was found that the signaled intersection had an average value of DS > 1, so for the service level at the intersection is the current forced / jammed with low speed. Where the largest queue length occurred 1876.7 m, an average delay of 210.30 SMP/ sec, and vehicles stopped at an average of 7378 SMP/hour. And for unsignalized intersections having an average DS <0.45, the service level at the intersection is a stable flow with operating speed starting to be limited by traffic conditions, this intersection has the greatest queue probability (QP%) 8.48-20.35 in the Saturday time period - afternoon and intersection delay 9.5 SMP / sec.